Sasi as a Lingat Village Government Strategy for the Preservation of Taripang in the Tanimbar Islands - Yohekbet Dorkas Wally; Titus Gaite; Jumiati Tuharea (CV. Rayyan Dwi Bharata, 2023)
Writing this thesis discusses